Material Religion and Church Architecture in Cultural Analysis: A Theoretical Shortcut - Wietschorke, Jens (Traditiones, 2018)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This paper provides some theoretical framework for the cultural analysis of church architecture. It suggests a classification of three basic research approaches: the symptomatic reading, praxeological analysis and ethnographic study of architecture. Furthermore, it is shown how these approaches of architectural research can be implemented with regard to sacred space. Overall, the paper underlines that a comprehensive cultural analysis of built structures has to make use of all the proposed concepts together. <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"><span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Članek ponuja teoretski okvir za kulturološko analizo cerkvene arhitekture. Predlaga tri osnovne raziskovalne pristope: simptomatično branje, prakseološko analizo in etnografsko raziskavo arhitekture. Pokaže, kako je mogoče te pristope raziskovanja arhitekture uporabiti v svetem prostoru. Poudarjeno je, da celovita kulturna analiza grajenih struktur lahko pridobi z upoštevanjem vseh predloženih konceptov skupaj.